Review of code blue system and audit - Patil, Vishwanath C.; Shah, Jignesh N.; Jedge, Prashant P.; Patil, Sanjivani V. (International Journal of Research in Medical Sciences, 2019)
Background: Code Blue systems are communication systems that ensure the most rapid and effective resuscitation of a patient in respiratory or cardiac arrest. Code blue was established in Bharati Hospital and Research Centre in Sept 2011 in order to reduce morbidity and mortality in wards. The aim of the study was to evaluate the current code blue system and suggest possible interventions to strengthen the system. Methods: It was retrospective observational descriptive study. The study population included all consecutive patients above the age of 18 years for whom code blue had been activated. Data was collected using code blue audit forms. The data was analysed using SPSS (Statistical Package for social sciences) software. Results: A total of 260 calls were made using the blue code system between September 2011 to December 2012. The most common place for blue code activation was casualty. The wards were next, followed by dialysis unit and OPD. The indications for code blue team activation were cardio-respiratory arrest (CRA) (88 patients, 33.84%), change in mental status (52 patients, 20%), road traffic accidents RTA (21, 8.07%), convulsions (29 patients 11.15%), chest pain (19 patients, 8.46%), breathlessness (18 patients,6.92%) and worry of staff about the patient (17 patients, 6.53%), presyncope (10 patients, 3.84%), and others (6 patients, 2.30%). The average response time was 1.58±0.96 minutes in our study. Survival rate was more in medical emergency group 46.15% than in CRA group 31.61%. Initial success rate was 35.2% and a final success rate was 34.6%. Conclusions: Establishment of code blue team in the hospital enabled us to provide timely resuscitation for patients who had “out of ICU” CRA. Further study is needed to establish the overall effectiveness and the optimal implementation of code blue teams. The increasing use of an existing service to review patients meeting blue code criteria requires repeated education and a periodic assessment of site-specific obstacles to utilization.